China's Looming Human Capital Crisis: Upper Secondary Educational Attainment Rates and the Middle-income Trap. (23rd November 2016) - Khor, Niny; Pang, Lihua; Liu, Chengfang; Chang, Fang; Mo, Di; Loyalka, Prashant; Rozelle, Scott
Abstract: Accumulation of human capital is indispensable to spur economic growth. If students fail to acquire needed skills, not only will they have a hard time finding high-wage employment in the future but the development of the economies in which they work may also stagnate owing to a shortage of human capital. The overall goal of this study is to try to understand if China is ready in terms of the education of its labour force to progress from middle-income to high-income country status. To achieve this goal, we seek to understand the share of the labour force that has attained at least some upper secondary schooling ( upper secondary attainment ) and to benchmark these educational attainment rates against the rates of the labour forces in other countries (e.g. high-income/OECD countries; a subset of G20 middle-income/BRICS countries). Using the sixth population census data, we are able to show that China's human capital is shockingly poor. In 2010, only 24 per cent of China's entire labour force (individuals aged 25–64) had ever attended upper secondary school. This rate is less than one-third of the average upper secondary attainment rate in OECD countries. China's overall upper secondary attainment rate and the attainment rate of its youngest workers (aged 25–34) is also the lowest of all the BRICS countries (with the exception of India for which data were not available). Our analysis also demonstrates that the statistics on upper secondary education reported by the Ministry of Education (MoE) are overestimated. In the paper, we document when MoE and census-based statistics diverge, and raise three possible policy-based reasons why officials may have begun to have an incentive to misreport in the mid-2000s. 摘要: 人力资本积累是促进经济发展至关重要的因素。如果劳动力的人力资本不足, 不仅难以找到高收入的工作, 国家经济发展也会因此停滞。本研究的主要目的是通过衡量和比较中国和其他国家 (经合组织成员国等高收入国家以及二十国集团和金砖四国等中等收入国家) 劳动力的中等教育水平 (包含高中和职高), 来了解中国目前的劳动力教育水平是否能够支持中国经济从中等收入向高等收入迈进。我们利用第六次人口普查数据分析显示中国的人力资本水平极低。 2010 年中国只有24%的劳动力 (25 到 64 岁人口) 上过高中或职高, 不足经合组织成员国的三分之一。中国总体劳动力中上过高中或职高的比例和相对年轻的劳动力 (25 到 34 岁人口) 中上过高中或职高的比例也是在金砖四国当中最低的 (因数据缺失该比较不含印度)。我们的分析也指明中国教育部过高估计了劳动力中等教育的普及程度。本文也探索了人口普查数据和教育部统计数据之间出现差异的时间截点以及出现这种对劳动力教育程度过高估计的原因。